2000
DOI: 10.1074/jbc.m909998199
|View full text |Cite
|
Sign up to set email alerts
|

The Homeodomain Protein Barx2 Contains Activator and Repressor Domains and Interacts with Members of the CREB Family

Abstract: Barx1 and Barx2 are homeodomain proteins originally identified using regulatory elements of genes encoding certain cell adhesion molecules (CAMs). In the present study, we characterize regions of Barx2 that bind to regulatory elements of genes encoding three CAMs, L1, neuron-glia CAM (Ng-CAM), and neural CAM (N-CAM), and identify domains of Barx2 that regulate N-CAM transcription. The homeodomain of Barx2 was sufficient for binding to homeodomain binding sites (HBS) from all three CAM genes. The presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 45 publications
5
31
0
Order By: Relevance
“…All probes were of comparable specific activity. EMSAs used 25,000 cpm of each probe and in vitro translated proteins, as described previously (3). Relative binding of the protein to the HBS probes was determined by measuring the intensity of the probe/protein complexes using a PhosphorImager (Molecular Dynamics).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…All probes were of comparable specific activity. EMSAs used 25,000 cpm of each probe and in vitro translated proteins, as described previously (3). Relative binding of the protein to the HBS probes was determined by measuring the intensity of the probe/protein complexes using a PhosphorImager (Molecular Dynamics).…”
Section: Methodsmentioning
confidence: 99%
“…Fragments-Like most homeodomain proteins, BARX2 binds to motifs that contain the core sequence, TAAT (3,6,19) however, further requirements for BARX2 binding have not been well defined. Earlier studies showed that BARX2 bound with high affinity to the HBS element from the murine Ncam1 promoter (3).…”
Section: Barx2 Binds Preferentially To Paired Taat Motifs Within Barxmentioning
confidence: 99%
See 3 more Smart Citations